Manufacturing method of high-safety lithium ion battery
By adding Al2O3 ceramic powder to the positive and negative electrode formula of lithium-ion batteries and using double-sided ceramic separators, and adding specific additives to the electrolyte, the safety accident caused by the internal short circuit of the lithium-ion battery is solved, and the safety of the battery is significantly improved Performance and stability.
Patent Information
- Application Number
- CN202411532145.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-14
AI Technical Summary
Lithium-ion batteries may have internal short circuits during use, resulting in serious safety accidents such as fires and explosions, limiting their widespread use in medical devices and other fields.
By adding Al2O3 ceramic powder to the positive and negative electrode formulas, using a double-sided ceramic separator, and adding specific additives such as FPOP, SN and HTCN to the electrolyte, a stable CEI film is formed to inhibit the positive electrode interface and electrolyte reaction, and enhance the battery safety performance.
It effectively improves the safety of lithium-ion batteries, reduces the risk of internal short circuits, improves the performance of the battery under high and low temperature conditions, and ensures the long-term stability and safety of the battery.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium battery production, and in particular to a method for manufacturing a high-safety lithium-ion battery. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density and cycle efficiency, low self-discharge, and no memory effect, and are widely used in modern society. For example, in portable electronic devices, from smartphones to laptops, the existence of lithium-ion batteries enables these devices to operate independently for a long time, meeting people's needs to use them anytime and anywhere. In the field of medical devices, lithium-ion batteries are widely used due to their high energy density and low self-consumption. However, the safety issues of lithium-ion batteries have always been an important factor restricting their further development. For example, the battery may have an internal short circuit during use. Once an internal short circuit occurs, it may cause serious safety accidents such as fire and explosion.
[0003] With the improvement of people's safety awareness and the continuous expansion of lithium-ion battery application scenarios, the research and development of high-safety lithium-ion batteries has become an inevitable trend. For example, in the field of medical devices, the safety of lithium-ion batteries is directly related to the life safety of users, and even a safety accident with a very small probability is unacceptable. Safety has become an important consideration for consumers when choosing battery products. At the same time, from the perspective of sustainable development, improving the safety of lithium-ion batteries will help reduce resource waste and environmental damage caused by battery safety accidents, which is conducive to the long-term and stable development of the lithium-ion battery industry. Summary of the invention
[0004] (I) Purpose of the invention
[0005] In view of this, the purpose of the present invention is to provide a method for manufacturing a high-safety lithium-ion battery, which solves the problems raised in the above background.
[0006] (II) Technical solution
[0007] A method for manufacturing a high-safety lithium-ion battery, comprising the steps of:
[0008] 1) Preparation of positive electrode:
[0009] The positive electrode sheet is composed of a positive electrode current collector and a positive electrode material coated on the positive electrode current collector; the positive electrode current collector is aluminum foil;
[0010] The positive electrode material includes a positive electrode active material, a binder, a conductive agent and Al2O3;
[0011] The positive electrode active material is one or a mixture of lithium cobalt oxide, ternary metal, lithium manganese oxide, and lithium iron phosphate, and the magnetic substance content of the positive electrode material is ≤30ppb and the water content is ≤300ppm;
[0012] The binder is high molecular weight PVDF, with a molecular weight of ≥ 1.1 million;
[0013] The conductive agent is one or more of conductive carbon fiber (VGCF), carbon nanotube (CNT), and conductive agent SP;
[0014] In the positive electrode material, the mass ratio of positive electrode active material, binder, conductive agent and Al2O3 is 95.0-97.5%: 1.0-1.5%: 1%-2%: 0.5%-1.5%;
[0015] During the preparation, the positive electrode active material, the binder, the conductive agent SP, Al2O3 and the solvent are mixed uniformly according to the above mass ratio to obtain the positive electrode slurry, and then the positive electrode slurry is uniformly coated on the surface of the aluminum foil, dried, and rolled to obtain the positive electrode sheet;
[0016] 2) Preparation of negative electrode sheet:
[0017] The negative electrode sheet is composed of negative electrode active material, CMC, binder, conductive agent, Al2O3 and copper foil;
[0018] The negative electrode active material is artificial graphite;
[0019] The binder is one or both of SBR (styrene-butadiene rubber latex) and PAA (polyacrylate);
[0020] The conductive agent is one or more of carbon nanotubes (CNT), conductive carbon fibers (VGCF), conductive carbon black, conductive graphite, acetylene black, and graphene composite conductive agents;
[0021] In the negative electrode sheet, the mass ratio of the negative electrode active material, CMC, binder, conductive agent, and Al2O3 is 94-94.5%: 1.2-1.5%: 0.5-1.5%: 1.5-2.0%: 0.5-1.5%;
[0022] During the preparation, the negative electrode active material, CMC, conductive agent, binder, Al2O3 and solvent are mixed evenly according to the above mass ratio to obtain negative electrode slurry, and then the negative electrode slurry is evenly coated on the surface of copper foil, dried, and rolled to obtain a negative electrode sheet;
[0023] 3) Preparation of battery cells:
[0024] After welding the tabs of the positive electrode sheet and the negative electrode sheet prepared above, the tabs are wound with the separator to obtain a winding core;
[0025] The core is baked at 85°C for 4 hours, and then packaged, baked, injected, formed, and divided into different volumes to obtain a battery cell.
[0026] The diaphragm is a double-sided ceramic diaphragm or a double-sided ceramic glue-coated diaphragm.
[0027] Preferably, the electrolyte is a safe electrolyte, the solvent comprises 10%-15% ethylene carbonate (EC), 30%-35% diethyl carbonate (DEC), 10%-15% propylene carbonate (PC), 20%-25% propyl propionate (PP), the additives comprise 2%-3% VC, 2%-3% PS, 0.5-1% LiBOB, 1-2% SN, 2-3% HTCN, 0.5-0.7% LiODFB, 0.1-0.3% FPOP, the electrolyte is LiPF6, the content is 1.1-1.2 mol, and the conductivity is ≥8.0 ms / cm.
[0028] Preferably, the processes of welding the pole ears, winding, packaging, and liquid injection of the lithium-ion battery adopt common processes in the industry.
[0029] Preferably, in the positive electrode slurry, the solid components include 96.0 wt% of positive electrode active material, 1.5 wt% of binder PVDF, 0.5 wt% of carbon nanotubes CNT, 0.5 wt% of conductive carbon SP, and 1.5 wt% of Al2O3.
[0030] Preferably, in the negative electrode slurry, the solid component includes 94.5wt% graphite, 1.5wt% CMC, 1.0wt% conductive carbon black, 1.5wt% Al2O3, and 1.5wt% SBR, and the solvent content is such that the solvent accounts for 110-120% of the total mass of the negative electrode slurry.
[0031] Preferably, the content of magnetic material in the battery core is ≤1ppm.
[0032] It can be seen from the above technical solutions that the present application has the following beneficial effects:
[0033] 1. The invention adds Al2O3 ceramic powder to its positive and negative electrode formulas to improve safety performance; uses a double-sided ceramic-coated diaphragm, which has small thermal shrinkage and strong puncture resistance, can effectively improve safety, control the moisture and magnetic substances of the material from the raw material end, and add a core baking process after winding, baking at 85°C for 4 hours; 1-2% SN, 0.5-1% LiBOB, 2-3% HTCN, 0.5-0.7% LiODFB, 0.1-0.3% FPOP and other additives are added to the electrolyte. The addition of SN and HTCN can form a stable CEI film on the positive electrode surface, inhibiting the reaction between the positive electrode interface and the electrolyte; the addition of ODFB improves the low-temperature conductivity and high-temperature stability of the electrolyte, taking into account the high and low temperature performance of the battery; the addition of FPOP can form a stable CEI film at the positive electrode interface, effectively inhibiting the occurrence of harmful side reactions, and FPOP has a good flame retardant effect. DETAILED DESCRIPTION
[0034] An embodiment provided by the present invention:
[0035] A method for manufacturing a high-safety lithium-ion battery, comprising the steps of:
[0036] 1) Preparation of positive electrode:
[0037] The positive electrode sheet is composed of a positive electrode current collector and a positive electrode material coated on the positive electrode current collector; the positive electrode current collector is aluminum foil;
[0038] The positive electrode material includes a positive electrode active material, a binder, a conductive agent and Al2O3;
[0039] The positive electrode active material is one or a mixture of lithium cobalt oxide, ternary, lithium manganese oxide, and lithium iron phosphate, and the magnetic substance content of the positive electrode material is ≤30ppb and the water content is ≤300ppm;
[0040] The binder is high molecular weight PVDF, with a molecular weight of ≥1.1 million;
[0041] The conductive agent is one or more of conductive carbon fiber (VGCF), carbon nanotube (CNT), and conductive agent SP;
[0042] In the positive electrode material, the mass ratio of positive electrode active material, binder, conductive agent and Al2O3 is 95.0-97.5%: 1.0-1.5%: 1%-2%: 0.5%-1.5%;
[0043] During the preparation, the positive electrode active material, the binder, the conductive agent SP, Al2O3 and the solvent are mixed uniformly according to the above mass ratio to obtain the positive electrode slurry, and then the positive electrode slurry is uniformly coated on the surface of the aluminum foil, dried, and rolled to obtain the positive electrode sheet;
[0044] 2) Preparation of negative electrode sheet:
[0045] The negative electrode sheet is composed of negative electrode active material, CMC, binder, conductive agent, Al2O3 and copper foil;
[0046] The negative electrode active material is artificial graphite;
[0047] The binder is one or both of SBR (styrene-butadiene rubber latex) and PAA (polyacrylate);
[0048] The conductive agent is one or more of carbon nanotubes (CNT), conductive carbon fibers (VGCF), conductive carbon black, conductive graphite, acetylene black, and graphene composite conductive agents;
[0049] In the negative electrode sheet, the mass ratio of negative electrode active material, CMC, binder, conductive agent and Al2O3 is 94-94.5%: 1.2-1.5%: 0.5-1.5%: 1.5-2.0%: 0.5-1.5%;
[0050] During the preparation, the negative electrode active material, CMC, conductive agent, binder, Al2O3 and solvent are mixed evenly according to the above mass ratio to obtain negative electrode slurry, and then the negative electrode slurry is evenly coated on the surface of copper foil, dried, and rolled to obtain a negative electrode sheet;
[0051] 3) Preparation of battery cells:
[0052] After welding the tabs of the positive electrode sheet and the negative electrode sheet prepared above, the tabs are wound with the separator to obtain a winding core;
[0053] The core is baked at 85°C for 4 hours, and then packaged, baked, injected, formed, and divided into different volumes to obtain a battery cell.
[0054] The diaphragm is a double-sided ceramic diaphragm or a double-sided ceramic glue-coated diaphragm.
[0055] Furthermore, the electrolyte is a safe electrolyte, the solvent includes 10%-15% ethylene carbonate (EC), 30%-35% diethyl carbonate (DEC), 10%-15% propylene carbonate (PC), 20%-25% propyl propionate (PP), the additives include 2%-3% VC, 2%-3% PS, 0.5-1% LiBOB, 1-2% SN, 2-3% HTCN, 0.5-0.7% LiODFB, 0.1-0.3% FPOP, the electrolyte is LiPF6, the content is 1.1-1.2 mol, and the conductivity is ≥8.0ms / cm.
[0056] Furthermore, the processes of welding the tabs, winding, packaging, and injecting lithium-ion batteries use common processes in the industry. Using common processes usually means that the required materials and equipment can be more easily obtained, which helps to reduce production costs and improve production efficiency.
[0057] Furthermore, in the positive electrode slurry, the solid components include 96.0 wt % of positive electrode active material, 1.5 wt % of binder PVDF, 0.5 wt % of carbon nanotubes CNT, 0.5 wt % of conductive carbon SP, and 1.5 wt % of Al 2 O 3 .
[0058] Furthermore, in the negative electrode slurry, the solid component includes 94.5wt% of graphite, 1.5wt% of CMC, 1.0wt% of conductive carbon black, 1.5wt% of Al2O3, and 1.5wt% of SBR, and the solvent content makes the solvent account for 110-120% of the total mass of the negative electrode slurry.
[0059] Furthermore, the content of magnetic material in the battery core is ≤1ppm.
[0060] The following is a description of the test method and comparative examples:
[0061] Example 1
[0062] The battery cell was obtained after adding 0.1% FPOP to the electrolyte, injecting, forming and dividing the capacity.
[0063] Example 2
[0064] The battery cell was obtained after adding 0.3% FPOP to the electrolyte, injecting, forming and dividing the capacity.
[0065] Example 3
[0066] The battery cell was obtained after adding 0.5% FPOP to the electrolyte, injecting, forming and dividing the capacity.
[0067] Comparative Example
[0068] The battery cell is obtained after electrolyte is injected, formed and divided without adding FPOP.
[0069] Test items: capacity, internal resistance, cycle performance, 1C6V overcharge, 0℃ charging high temperature short circuit test, 0℃ charging thermal shock test.
[0070] From the data in Table 1.1 to Table 1.5, it can be seen that the performance is best when FPOP is added at 0.3%. After adding FPOP to the electrolyte, FPOP preferentially generates a thinner and more uniform CEI film on the surface of the positive electrode to protect the positive electrode material. The battery capacity and cycle performance can be improved within a certain concentration range. From the data, the capacity and cycle performance are best when the addition amount is 0.3%. After adding 0.5%, the capacity and cycle performance decrease. FPOP has a good flame retardant effect. After the addition amount reaches 0.3%, 1C6V overcharge, 0℃ charging, 55℃ high temperature short circuit and thermal shock tests are 100% passed. This design invention improves the safety performance of the battery by adding Al2O3 to the positive and negative electrode formulas, using double-sided ceramic diaphragms and electrolyte design.
[0071] The following table shows the test data of the embodiments and comparative examples:
[0072] Capacity and internal resistance data
[0073]
[0074] Table 1.10.5C charge and discharge cycles 500 times
[0075]
[0076] Table 1.21C6V overcharge test
[0077]
[0078] Table 1. 30℃ charging, 55℃ high temperature short circuit test
[0079]
[0080] Table 1. 40℃ charging, 130℃ thermal shock test
[0081]
[0082]
[0083] Table 1.5
[0084] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for manufacturing a high-safety lithium-ion battery, characterized in that: The invention comprises a high-safety lithium-ion battery composed of a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte, and includes the following steps: 1) Preparation of positive electrode: The positive electrode sheet is composed of a positive electrode current collector and a positive electrode material coated on the positive electrode current collector; the positive electrode current collector is aluminum foil; The positive electrode material comprises a positive electrode active material, a binder, a conductive agent and Al2O3; The positive electrode active material is one or a mixture of lithium cobalt oxide, ternary metal, lithium manganese oxide, and lithium iron phosphate, and the magnetic substance content of the positive electrode material is ≤30ppb and the water content is ≤300ppm; The binder is high molecular weight PVDF, with a molecular weight of ≥ 1.1 million; The conductive agent is one or more of conductive carbon fiber (VGCF), carbon nanotube (CNT), and conductive agent SP; In the positive electrode material, the mass ratio of positive electrode active material, binder, conductive agent and Al2O3 is 95.0-97.5%: 1.0-1.5%: 1%-2%: 0.5%-1.5%; During the preparation, the positive electrode active material, the binder, the conductive agent SP, Al2O3 and the solvent are mixed uniformly according to the above mass ratio to obtain the positive electrode slurry, and then the positive electrode slurry is uniformly coated on the surface of the aluminum foil, dried, and rolled to obtain the positive electrode sheet; 2) Preparation of negative electrode sheet: The negative electrode sheet is composed of negative electrode active material, CMC, binder, conductive agent, Al2O3 and copper foil; The negative electrode active material is artificial graphite; The binder is one or both of SBR (styrene-butadiene rubber latex) and PAA (polyacrylate); The conductive agent is one or more of carbon nanotubes (CNT), conductive carbon fibers (VGCF), conductive carbon black, conductive graphite, acetylene black, and graphene composite conductive agents; In the negative electrode sheet, the mass ratio of the negative electrode active material, CMC, binder, conductive agent, and Al2O3 is 94-94.5%: 1.2-1.5%: 0.5-1.5%: 1.5-2.0%: 0.5-1.5%; During the preparation, the negative electrode active material, CMC, conductive agent, binder, Al2O3 and solvent are mixed evenly according to the above mass ratio to obtain negative electrode slurry, and then the negative electrode slurry is evenly coated on the surface of copper foil, dried, and rolled to obtain a negative electrode sheet; 3) Preparation of battery cells: After welding the tabs of the positive electrode sheet and the negative electrode sheet prepared above, the tabs are wound with the separator to obtain a winding core; The core is baked at 85°C for 4 hours, and then packaged, baked, injected, formed, and divided into different volumes to obtain a battery cell. The diaphragm is a double-sided ceramic diaphragm or a double-sided ceramic glue-coated diaphragm.
2. The method for manufacturing a high-safety lithium-ion battery according to claim 1, characterized in that: The electrolyte is a safe electrolyte, the solvent includes 10%-15% ethylene carbonate (EC), 30%-35% diethyl carbonate (DEC), 10%-15% propylene carbonate (PC), 20%-25% propyl propionate (PP), the additives include 2%-3% VC, 2%-3% PS, 0.5-1% LiBOB, 1-2% SN, 2-3% HTCN, 0.5-0.7% LiODFB, 0.1-0.3% FPOP, the electrolyte is LiPF6, the content is 1.1-1.2 mol, and the conductivity is ≥8.0 ms / cm.
3. The method for manufacturing a high-safety lithium-ion battery according to claim 1, characterized in that: The processes of welding the pole ears, winding, packaging, and liquid injection of the lithium-ion battery adopt the common processes in the industry.
4. The method for manufacturing a high-safety lithium-ion battery according to claim 1, characterized in that: In the positive electrode slurry, the solid components include 96.0 wt % of positive electrode active material, 1.5 wt % of binder PVDF, 0.5 wt % of carbon nanotubes CNT, 0.5 wt % of conductive carbon SP, and 1.5 wt % of Al2O3.
5. The method for manufacturing a high-safety lithium-ion battery according to claim 1, characterized in that: In the negative electrode slurry, the solid components include 94.5wt% graphite, 1.5wt% CMC, 1.0wt% conductive carbon black, 1.5wt% Al2O3, and 1.5wt% SBR, and the solvent content makes the solvent account for 110-120% of the total mass of the negative electrode slurry.
6. The method for manufacturing a high-safety lithium-ion battery according to claim 1, characterized in that: The content of magnetic material in the battery core is ≤1ppm.
Citation Information
Cited By
Safe silicon-carbon negative electrode lithium ion battery and preparation method thereof
CN121097176A